(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: To assess the knowledge, attitude and practices regarding AIDS. Background: AIDS is a disease of human immune system. By year 2009 there were more than 33.4 million people world-wide affected by HIV/AIDS with 2.7 million new HIV/AIDS infections per year and 2 million annuals deaths. The economic burden of this disease is far more than anticipated. The recent data shows there are 98,000 HIV-infected people living in Pakistan. Methods: A cross-sectional survey was conducted directed to people in Lahore. The survey assessed the knowledge, attitude and practice of the people regarding HIV/AIDS on the basis of cohort’s sex, age and level of education. Data was then analyzed using SPSS and p-values were estimated using Chi-squared test. Results: A total of 50 individuals were surveyed. Our study showed that individuals with under matriculation education were less aware of the concept of AIDS(p=0.002), less aware of its prevention methods(p=0.002) and less likely to seek knowledge regarding HIV/AIDS(p=0.027).Male individuals were more likely to have screening for HIV/AIDS(p=0.027). Individuals aged above 25 years were more likely to have intra-venous drug use history(p=0.004). Conclusion: Study cohort was well aware about the disease and its usual modes of transmission irrespective of their sex, age or education. Our study showed people generally wanted to practice safe sex, be restricted to their life partners. People also showed willingness to educate their children early about AIDS. However, more work is required to increase the level of education as this has impact on the awareness and notions of the individuals regarding AIDS.